HUMAN RELATIONS ACTIVITIES OF RW MANAGEMENTS IN BUILDING THE LIFE OF HARMONY OF CITIZENS - Rifqi Zaeni Achmad Syam; Nita Kanya; Willya Achmad (Sean Institute, 2023)
Research entitled Human Relations Activities of RW Managements in Building the Life of Harmony of Citizen, in carrying out this research, the authors focused on human relations activities carried out by RW 08 Managements, Antapani Wetan Village, Bandung City. The author's reason for choosing this place is because the writer lives in the housing complex so that it can facilitate the implementation of observations and interviews in collecting data. The purpose of this study was to determine the human relations activity program, the intensity of the human relations program, the credibility of the communicator in fostering community harmony, as well as the quality of human relations activities of RW Managements in fostering community harmony. Furthermore, in this study the authors used qualitative methods where the research was based on the case of the research object. The author used the research object, namely community members in RW 08, Antapani Wetan Village, while the sample used was purposive sampling where the sample was determined intentionally by the researcher on the basis of certain criteria/considerations. Furthermore, in data collection techniques used were interviews, observation, literature testing. and documentation study, after carrying out this research it can be interpreted that the role of the management of RW 08, Antapani Wetan Village, Bandung City in accordance with their position, main tasks and functions is able to carry out human relations properly so that harmony among citizens can be realized.